HUBUNGAN DERIVASI PRIME NEAR-RING DENGAN SIFAT KOMUTATIF RING - TRIWULANDARI, PRADITA Z.; SARI, KARTIKA; HARINI, LUH PUTU IDA (E-Jurnal Matematika, 2017)
Near-rings are generalize from rings. A research on near-ring is continous included a research on prime near-rings and one of this research is about derivation on prime near-rings. This article will reviewing about relation between derivation on prime near-rings and commutativity in rings with literature review method . The result is prime near-rings  are commutative rings if a nonzero derivation d on N hold one of this following conditions: (i) , (ii) , (iii) , (iv) , (v) , (vi) , for all , with  is non zero semigroup ideal from .